Mind the gap: responding to the global funding crisis in family planning. Issue 3 (1st July 2004) - Gribble, James N; Jennings, Victoria; Nikula, Minna
Abstract : The widening gap between the cost of meeting family planning needs and the funding available for commodities and programmes is a concern among policymakers and reproductive health professionals. The gap could reach US$210 million by 2015. Its causes are clear; its solutions are not. While changes in programme method mix and cost shifting could address this gap, an often-overlooked alternative is the development and introduction of effective, low-cost methods. The Standard Days Method™ (SDM) has a first-year failure rate of only 4.8 (correct use) and is acceptable to many women around the world. It is easily integrated into programmes. Many SDM users rely on CycleBeads™ to help identify the days when pregnancy is likely. Though already meeting couples' needs in many places, the SDM responds in a unique way to needs in settings with high use of traditional methods, high levels of unmet need, and chronic depletion of commodities. The donor gap could have negative consequences, but it also facilitates reassessing family planning programme policies to include other effective, low-cost methods.